MEDIA PEMBELAJARAN VISUAL SENI RUPA PADA ANAK PAUD/TK - Ana Rosmiati (Institut Seni Indonesia Surakarta, 2011)
Visual media is the most appropriate means to assist learning methods in early childhood. One way to use media arts to help young children develop skills abilities of children. Besides that, the media arts help educators and parents to facilitate a concrete method of teaching can stimulate students’ motivation. This research will explore the use of models of visual media arts learning for children kindergarten and the impact of the use of visual media art in children’s learning kindergarten. The method of this study include data collection, data analysis, and presentation of data analysis. This study used analysis techniques with step-by-step interactive model, which consists of three components analysis, namely data reduction, data presentation, and drawing conclusions or verification. Learning method that uses art media include drawing or painting, make a stamp from a variety of media, linking material by hand, drawing techniques with collage, and pin the pattern. Key words : media, art, model, learning.